Complex temperature distribution model for controlling the thermal performance of household led lamps - V. P. Kuzmenko (Омский научный вестник)
The study covers the question of the dynamics of heat transfer in a household LED lamp and scenarios for simplifying the modeling of thermal distribution, including the account of heat conduction, convection and the influence of several LED light sources. A comprehensive analysis of heat distribution processes in household LED lamps and the development of a mathematical model of the thermal radiation of an LED light source using the finite difference method are presented. The developed model takes into account the lamp geometry, material properties and environmental conditions. Special attention is paid to the influence of the location of the LEDs in the lamp system. The novelty of the study lies in the fact that the volumetric geometry of the lamp and light source, scenarios to account for various parameters of the model are included in the mathematical model. Verification of the model has shown accuracy up to 93 %. The study aims to create a more realistic and accurate method for modeling and analyzing thermal management in multilight LED household lighting fixtures.